Identification of Chimeric RNAs in Pig Skeletal Muscle and Transcriptomic Analysis of Chimeric RNA TNNI2-ACTA1 V1 - Liu, Dongyu; Xia, Jiqiao; Yang, Zewei; Zhao, Xuelian; Li, Jiaxin; Hao, Wanjun; Yang, Xiuqin (Frontiers in Veterinary Science, 2021)
In past studies, the chimeric RNA was considered a special marker of cancer. However, this view has been challenged, as with the development of high-throughput technology, the chimeric RNAs in mounting numbers are identified in normal tissues. Two bioinformatic software, Star-Fusion and Fusionmap were used to jointly predict 49 Chimeric RNAs in this study. A chimeric RNA TNNI2-ACTA1 and its 8 transcript variants were identified by RT-PCR. We found that the chimeric RNA TNNI2-ACTA1 V1 can inhibit the proliferation of porcine skeletal muscle satellite cells (PSCs) by CCK-8 assay, EdU assay and flow cytometry. However, as parental genes, there is no such effect in the group TNNI2 and ACTA1. To explore the underlying mechanism for this phenomenon, the level of the differential gene expression under the overexpression of TNNI2-ACTA1 V1, TNNI2, and ACTA1 were investigated using transcriptome analysis. Compared with the negative control group (NC), 1592 differentially expressed genes (DEGs) enhanced expression and 1077 DEGs declined expression in the group of TNNI2, 1226 DEGs enhanced expression and 902 DEGs declined expression in the group of ACTA1, and 13 DEGs enhanced expression and 16 DEGs declined expression in the group of TNNI2-ACTA1 V1, respectively. Compared with the parental gene groups, there are three enriched specific genes in the TNNI2-ACTA1 V1 group (NCOA3, Radixin, and DDR2). These three genes may be the key to TNNI2-ACTA1 V1 regulating cell proliferation. Taken together, our study explores the role of chimeric RNAs in normal tissues. Additionally, our study as the first research provides the foundation for the mechanism of the chimeric RNAs regulating porcine skeletal muscle growth.